(untitled) (Academia Journal of Medicine, 2019)
Background: An increased prevalence of vitamin D deficiency has been reported from across the globe including India. Various studies have shown an intrinsic relation between various parameters of maternal and fetal wellbeing with maternal vitamin D status during pregnancy. Aims: To prospectively assess the vitamin D nutritive status in pregnant women in North district of Kashmir Valley and to study the prevalence of suboptimal vitamin D status in apparently healthy pregnant North Kashmiri women.Study Design: Sixty three consenting pregnant women attending the antenatal clinic of the DH Baramulla and Endocrine OPD over the study period of 12 months were enrolled. Subjects and Methods: The subjects underwent a detailed history and physical examination as per a pre-formed Performa. History was focused on occupation, dietary history including diet taken in last 24 hours, exposure to sunlight, drug intake, menstrual history and history of any systemic illness. A particular record was made of the women’s dressing habits. Of the 63 subjects recruited, only 60 subjects (in whom Vitamin D levels could be estimated) were further analyzed for the study. Serum levels of [25 (OH) D] were estimated by 25-OH-D assay, an RIA based procedure. Results: In the present study, vitamin D insufficiency (defined as serum 25[OH] D levels <30 ng/ml) was observed in about 98.2 % of pregnant North Kashmiri women while as vitamin D deficiency (serum 25[OH] D <20 ng/ml)2 was observed in 71.6 %. In only about 3.2 % subjects vitamin D sufficiency (serum 25[OH] D >30 ng/ml) was observed. Conclusion: From our study we conclude that vitamin D deficiency is quite prevalent in normal pregnant women in North Kashmir valley. Taking a cut off value of 25 (OH) D of less than 20 ng/ml as vitamin D deficiency, overall 98 % of pregnant women were found to be vitamin D deficient.